2010
DOI: 10.1016/j.nbd.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ictogenesis and parahippocampal networks in a rodent model of temporal lobe epilepsy

Abstract: Temporal lobe epilepsy (TLE) is a chronic epileptic disorder involving the hippocampal formation. Details on the interactions between the hippocampus proper and parahippocampal networks during ictogenesis remain, however, unclear. In addition, recent findings have shown that epileptic limbic networks maintained in vitro are paradoxically less responsive than non-epileptic control (NEC) tissue to application of the convulsant drug 4-aminopyridine (4AP). Field potential recordings allowed us to establish here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 66 publications
(100 reference statements)
2
36
1
2
Order By: Relevance
“…They showed that 50 μM 4AP could induce seizure-like events in the medial EC in only 20% of pilocarpine-treated slices. In contrast, we have previously reported that epileptic slices generate robust ictal-like activity in response to 4AP treatment (Panuccio et al, 2010). In our present experiments as well, we observed seizure-like events in all EC and in 72% of PC recordings from epileptic slices using the same concentration of 4AP.…”
Section: Ap-induced Epileptiform Discharges In Control and Epilepticcontrasting
confidence: 60%
See 2 more Smart Citations
“…They showed that 50 μM 4AP could induce seizure-like events in the medial EC in only 20% of pilocarpine-treated slices. In contrast, we have previously reported that epileptic slices generate robust ictal-like activity in response to 4AP treatment (Panuccio et al, 2010). In our present experiments as well, we observed seizure-like events in all EC and in 72% of PC recordings from epileptic slices using the same concentration of 4AP.…”
Section: Ap-induced Epileptiform Discharges In Control and Epilepticcontrasting
confidence: 60%
“…1C). We previously reported that epileptiform discharges were less frequent and more robust in pilocarpine-treated EC compared to NEC tissue when recorded later in the chronic period (Panuccio et al, 2010).…”
Section: Ap-induced Epileptiform Activity In Nec and Epileptic Tissuementioning
confidence: 93%
See 1 more Smart Citation
“…It was shown in these studies that (i) ictal discharges -which are consistently initiated by parahippocampal neuronal networks -disappear over 1-2 h of bath application of 4AP or Mg 2+ -free medium, while (ii) CA3-driven, fast interictal activity continues to occur throughout the experiment (Barbarosie and Avoli, 1997;Barbarosie et al, 2000Barbarosie et al, , 2002D'Antuono et al, 2002;Benini et al, 2003;Panuccio et al, 2010). In these experiments, Schaffer collateral cut restores ictal activity generation thus suggesting that CA3-driven interictal activity exerts an unexpected "inhibitory" effect on the expression of ictal discharges in structures such as the entorhinal cortex, the amygdala and even the insular cortex.…”
Section: Ca3-driven Outputs Control the Expression Of Gabaergic Synchmentioning
confidence: 97%
“…These changes -which may lead to limbic seizures in vivo and perhaps in patients presenting with TLE -consist of a decreased control exerted by hippocampal outputs on entorhinal cortex excitability along with reverberant activity between entorhinal cortex and CA1/subiculum networks (D' Antuono et al, 2002;Wozny et al, 2005a;Panuccio et al, 2010). The functional integrity of hippocampal neurons that contribute to the generation of normal output activity may thus represent a critical control point for limbic seizure generation and recurrence.…”
Section: Gaba a Receptor-mediated Inhibition May Implement Epileptifomentioning
confidence: 99%